Pengaruh Brand Image dan Kepercayaan terhadap Kepuasan Pelanggan Indihome PT. Telkomsel Bontang - Sari, Ayu Dita; Manurung, Ferdo Antonius (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to investigate the influence of brand image and trust on customer satisfaction in IndiHome PT. Telkomsel Bontang. Brand image and trust are key factors in shaping customer perceptions and loyalty in the telecommunications service industry. This research employs a quantitative approach using a questionnaire as the data collection instrument. The research sample consists of customers using IndiHome services in the Bontang region. The collected data is analyzed using multiple linear regression analysis. The results indicate that brand image has a significant positive influence on customer satisfaction. The more positive the customers' perceptions of the IndiHome brand image, the higher their level of satisfaction with the service. Furthermore, trust is also found to have a positive and significant impact on customer satisfaction. Customers who trust IndiHome tend to have higher levels of satisfaction. These findings indicate the importance of brand management and efforts to build customer trust in enhancing customer satisfaction in the telecommunications industry. Keywords: Brand Image, Customer Satisfaction, IndiHome, PT. Telkomsel Bontang, Trust.